2021
DOI: 10.1186/s12883-021-02050-w
|View full text |Cite
|
Sign up to set email alerts
|

Acute recurrent rhabdomyolysis in a Chinese boy associated with a novel compound heterozygous LPIN1 variant: a case report

Abstract: Background LPIN1-related acute recurrent rhabdomyolysis (RM), first reported in 2008, is an autosomal recessive inherited metabolic disease. In recent years, LPIN1 gene variants have been identified as one of the main causes of severe RM in children in Western countries. The disease is extremely rare in China, and we report a case of acute recurrent RM caused by a novel compound heterozygous LPIN1 variant. Case presentation A 15-year-old Chinese bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Degradation of Lipin 1 via the ubiquitin–proteasome system mediates lipogenesis, fibrogenesis, and TGF-β signaling in liver cells [ 34 , 35 ]. Several studies have shown that Lipin 1 deficiency is linked to recurrent rhabdomyolysis in human children [ 38 , 39 , 40 , 41 , 42 ], suggesting that Lipin 1 PAP activity is involved in the acute syndromes of rhabdomyolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of Lipin 1 via the ubiquitin–proteasome system mediates lipogenesis, fibrogenesis, and TGF-β signaling in liver cells [ 34 , 35 ]. Several studies have shown that Lipin 1 deficiency is linked to recurrent rhabdomyolysis in human children [ 38 , 39 , 40 , 41 , 42 ], suggesting that Lipin 1 PAP activity is involved in the acute syndromes of rhabdomyolysis.…”
Section: Introductionmentioning
confidence: 99%
“…
BACKGROUNDElevated serum creatine kinase (CK) could indicate muscle cell damage due to muscle trauma, strenuous exercise, or the use of certain drugs. [1][2][3] Numerous cytoplasmic components within muscle cells exit through the damaged sarcolemma, including myoglobin and electrolytes, which are involved in acute kidney injury (AKI) and possible cardiac dysrhythmia. 1,4,5 Motor signs associated with seizures, including tonic, clonic, and myoclonic movements, can be considered muscle overuse.
…”
mentioning
confidence: 99%